2016
DOI: 10.1186/s12939-016-0308-x
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening national capacities for researching on Social Determinants of Health (SDH) towards informing and addressing health inequities in Tanzania

Abstract: BackgroundTanzania’s socio-economic development is challenged by sharp inequities between and within urban and rural areas, and among different socio-economic groups. This paper discusses the importance of strengthening SDH research, knowledge, relevant capacities and responsive systems towards addressing health inequities in Tanzania.MethodsBased on a conceptual framework for building SDH research capacity, a mapping of existing research systems was undertaken between February and June 2012. It involved a rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…These respective asymmetries in the global scientific output and collaborations appear to mirror the geopolitical hierarchies and the subsequent dependencies and conditionalities that are known to have been created over time; it is surely no coincidence that the countries known for being international funding sources and also the countries at the core of these global research collaborations [ 76 78 ] and those known to be more 'dependent' on external research funding are on the periphery. In many lower income countries, the majority of research is externally funded, which may play a role in fostering and influencing the types of domestic vs. international research collaborations that are built, as well as potentially creating donor-driven research agendas that may influence policy agendas, and decisions on national research priorities, which may not necessarily correspond to local population needs [ 29 , 30 , 38 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…These respective asymmetries in the global scientific output and collaborations appear to mirror the geopolitical hierarchies and the subsequent dependencies and conditionalities that are known to have been created over time; it is surely no coincidence that the countries known for being international funding sources and also the countries at the core of these global research collaborations [ 76 78 ] and those known to be more 'dependent' on external research funding are on the periphery. In many lower income countries, the majority of research is externally funded, which may play a role in fostering and influencing the types of domestic vs. international research collaborations that are built, as well as potentially creating donor-driven research agendas that may influence policy agendas, and decisions on national research priorities, which may not necessarily correspond to local population needs [ 29 , 30 , 38 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…As found in this study, religion and ethnicity may play a significant role towards inequity in immunization coverage. Health inequity is known to be a set back to the wider health development, and this could be addressed by examining the wider social and structural aspects that increase vulnerability to diseases [ 30 – 33 ]. Evidence in Nigeria indicates that the community tailored interventions have proven to be effective in increasing the utilization of polio vaccination [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the health outcomes of a person and population are related to the structural determinants and conditions of daily life that comprise the SDH and are responsible for the majority of health inequities between and within countries (UN Economic and Social Council (UNECOSOC) 2000). Mtenga et al (2016) studied how strengthening SDH was important for addressing health inequities in Tanzania, as there are significant discrepancies within urban and rural areas with a direct impact on access to health care. They found that the majority of research in Tanzania fails to consider the context-specific structural determinants of health and inequities that provide a broader understanding of existing vulnerabilities.…”
Section: Stigma and Social Determinants Of Healthmentioning
confidence: 99%
“…A second way in which health systems differentially impacted these mothers and their children was in a lack of direct access to the health services required by persons with albinism that leads to health inequities (Mtenga et al 2016). Decreased access, particularly to skin and vision clinics, was pronounced in rural settings and for those living in poverty.…”
Section: Health Systems As a Social Determinant Of Healthmentioning
confidence: 99%
See 1 more Smart Citation